The Implication or Validity of the Rebound Effect in Present European Energy Sector - Bayramov, Tofig; Mammadli, Sabuhi (Studia Mundi – Economica, 2024)
Energy efficiency is one of the most important and global topics which is explored and studied. As a result of those studies, rebound effect has become important phenomenon due to failure of previous energy policies in stabilizing energy consumption levels. Based on rebound effect phenomenon, every energy legislature does not improve energy efficient, on the contrary it creates reverse effects. Recent energy policies are aimed to achieve a successful transition from conventional energy sources to renewables. Meanwhile, environmental challenges have increased the urgency and importance of latest steps. EU governance bodies have ratified several policies in tackling energy problems including rebound effect. This article explores how this phenomenon can result in undesired outcomes by studying possible effects of several variables in final energy consumption levels. These variables have been picked based on the potential impact factors on energy. We will implore desktop secondary research methodology to investigate to what extent EU energy policies have been successful in recent years to achieve energy efficiency. Afterwards, we can answer to our question whether rebound effect phenomenon is actual.